Association Between Macronutrients Intake and Depression in the United States and South Korea - Oh, Jihoon; Yun, Kyongsik; Chae, Jeong-Ho; Kim, Tae-Suk (Frontiers in Psychiatry, 2020)
Although the risk for depression appears to be related to daily dietary habits, how the proportion of major macronutrients affects the occurrence of depression remains largely unknown. This study aims to estimate the association between macronutrients (i.e., carbohydrate, protein, fat) and depression through national survey datasets from the United States and South Korea. Association between the prevalence of depression and each macronutrient was measured from 60,935 participants from the National Health and Nutrition Examination Survey (NHANES) and 15,700 participants from the South Korea NHANES (K-NHANES) databases. When the proportion of calories intake by protein increased by 10%, the prevalence of depression was significantly reduced both in the United States (Odds Ratio, OR [95% CI], 0.621 [0.530-0.728]) and South Korea (0.703 [0.397-0.994]). An association between carbohydrate intake and the prevalence of depression was seen in the United States (1.194 [1.116-1.277]), but not in South Korea. Fat intake was not significantly associated with depression in either country. Subsequent analysis showed that the low protein intake groups had significantly higher risk for depression than the normal protein intake groups in both the United States (1.648 [1.179-2.304]) and South Korea (3.169 [1.598-6.286]). In the daily diet of macronutrients, the proportion of protein intake is significantly associated with the prevalence of depression. These associations were more prominent in adults with insufficient protein intake, and the pattern of association between macronutrients and depression in Asian American and South Korean populations were similar. Our findings suggest that the proportion of macronutrients intake in everyday life may be related to the occurrence of depression.